2006
DOI: 10.1111/j.1469-7610.2006.01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicaraguan Sign Language and Theory of Mind: the issue of critical periods and abilities

Abstract: Background:  Previous studies in the literature report that deaf individuals who experience late access to language perform poorly on false belief tests of Theory of Mind (ToM) compared with age‐matched deaf and hearing controls exposed to language early. Methods:  A group of 22 deaf Nicaraguans (aged 7 to 39 years) who learned Nicaraguan Sign Language (ISN) at different ages were tested on a false belief and a nonverbal cartoon retell task designed to elicit talk about the contents of character's mental state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
2
35
2
1
Order By: Relevance
“…Moreover, even after accounting for the child's own language skills, the child's performance on the false belief task is independently predicted by the mother's proficiency with sign language, and specifically her use of mental EDITORIAL iii state words (Moeller & Schick, 2006). A recent investigation of Nicaraguan Sign Language suggests that performance on non-verbal false belief tasks is predicted by the age at which the child first learned sign language, and not by the number of years that they have been using it (Morgan & Kegl, 2006); children who first entered the sign language community before age 8 perform significantly better than those who did so later in life. Deaf children of native signers *who learn sign language from birth *show no delay at all (de Villiers, 2005).…”
Section: What Is the Role Of Language In Tom?mentioning
confidence: 97%
“…Moreover, even after accounting for the child's own language skills, the child's performance on the false belief task is independently predicted by the mother's proficiency with sign language, and specifically her use of mental EDITORIAL iii state words (Moeller & Schick, 2006). A recent investigation of Nicaraguan Sign Language suggests that performance on non-verbal false belief tasks is predicted by the age at which the child first learned sign language, and not by the number of years that they have been using it (Morgan & Kegl, 2006); children who first entered the sign language community before age 8 perform significantly better than those who did so later in life. Deaf children of native signers *who learn sign language from birth *show no delay at all (de Villiers, 2005).…”
Section: What Is the Role Of Language In Tom?mentioning
confidence: 97%
“…In the early stages of social cognitive development these children, even with early cochlear implants might experience a different quality of conversation and interaction during the period their parents adapt to their infant's deafness. Many previous studies have reported that deaf children aged 4 years and above and from hearing families who do not use sign language effectively, display a protracted delay in Conversational input to deaf children 4 Theory of Mind (ToM) reasoning on explicit tests (Courtin & Melot, 2005;Figueras-Costa & Harris, 2001;Meristo, Hjelmquist, Surian & Siegal, in press;Morgan & Kegl, 2006;Pyers & Senghas, 2009;Peterson & Siegal, 1995, 1999Schick, de Villiers, de Villiers, & Hoffmeister, 2007;Woolfe, Want, & Siegal, 2002). In elicited response methodologies the child is explicitly required to respond overtly to a question or prompt about the mental states of another person in the test.…”
Section: Conversational Input To Deaf Childrenmentioning
confidence: 99%
“…Just as children acquire language and theory of mind (ToM) according to distinct but typical developmental patterns, they also acquire the significant features of their own cultures (beliefs, behaviours, rituals, etc.) in a predictable progression of maturation (Morgan & Kegl 2006). The process of enculturation could potentially have innate features -perhaps we also have a 'universal grammar' for religion as we do for language (Alcorta 2006;Bloom 2007;Bulbulia 2005).…”
Section: Religion As Medium For Social Processesmentioning
confidence: 99%